Mental health nurses’ views of ward readmission: A focus group study in Brunei Darussalam - Haji Kassim, Karmayunika Khamsiah; Haji Md Safar, Mas Salina; Lupat, Agong; Zolkefli, Yusrita (Belitung Nursing Journal, 2021)
Background: Readmission becomes inevitable with the vast development of mental health services worldwide and the challenges faced by mental health services. This readmission is often caused by a relapse from an illness whereby the psychiatric patient needs nursing care. Objective: This study aimed to explore psychiatric nurses’ perceptions of reasons for readmission and nurses’ further role in reducing readmission. Methods: In this descriptive qualitative study, thematic analysis of five focus group discussions (n= 24 nurses) in one psychiatric department in Brunei Darussalam was identified through purposive sampling. Results: The nurses perceived the role of family and non-adherence to medication as a significant reason for psychiatric readmission. Simultaneously, nurses viewed that it was necessary to implement systematicchoeducation to strengthen the role of family and community service support to curb readmission rates. Conclusion: The phenomenon of mental health readmission impacts psychiatric nurses due to many stressful challenges with nurses wishing to respond personally, humanely and professionally. These challenges require suitable interventions, such as debriefing to ensure that nurses continuously strive to deliver quality care to psychiatric readmission patients.